Effect of Business Coaching on Growth and Performance and the Moderating Role of Competitive Advantage in Small Medium Enterprises in Malaysia - Azizan, Osman (2022)
High-impact growth is vital to the survival and sustainability of all small and medium enterprises (SMEs). Unfortunately, most SMEs' leaders do not invest sufficient time and resources in building employee competencies and assuring their organisations' high-impact growth. In Malaysia, an inadequacy of business coaching in the nation's SMEs necessitates more research into the effects of business coaching on the high-impact growth of SMEs. This study aimed to examine the effects of motivation, productivity, job satisfaction, innovation, and business model innovation on the growth and performance of SMEs in Malaysia and the moderating role of competitive advantage. A positivist philosophical approach was employed to investigate the effect of business coaching on growth and performance and the moderating role of competitive advantage in SMEs. Besides, this study adopted a causal research design. A survey questionnaire was utilised to collect data from respondents, while structural equation modelling was employed to analyse the data. According to the study's findings, motivation, productivity, innovation, and improved business model innovations positively and significantly influence the growth and performance of Malaysian SMEs. The study's findings also revealed that comparative advantage has a positive and significant influence on Malaysian SMEs' growth and performance. The findings of this study enlighten SME leaders in Malaysia and other stakeholders on the value of business coaching on the growth and performance and the key role of competitive advantage in Malaysian SMEs. The findings also have critical implications for business coaching among SMEs. The study posits that Malaysian SME leaders should promote motivation, productivity, job satisfaction, innovation, and improved business model innovations in their businesses to realise improved growth and performance.